An Interim Assessment of Ukrainian Output Developments, 2000-01 - De Vrijer, J. E. J. (IMF Working Papers; Working Paper ;, 2002)
After a long period of steep decline which followed the breakup of the Soviet Union, Ukraine's economy rebounded in 2000, and the recovery accelerated in 2001. The paper examines the timing and the nature of the recovery from a number of different perspectives such as the presence of idle but productive capital, the stance of domestic policies, real wage developments, learning, and foreign factors. The final chapter presents tentative conclusions, which point to an eclectic explanation involving a range of factors rather then any single major cause of the recovery, as well as an agenda for further research.